Wisatawan Perbatasan Serta Gambaran Masyarakat Perbatasan di Kabupaten Bintan dan Karimun di Kepulauan Riau - Zakia Ayu Lestari; I Wayan Thariqy Kawakibi Pristiwasa; M Fathurrahman Nurul Hakim; Emmita Devi Hari Putri (Journal of Tourism and Economic, 2023)
Bintan is one of the districts in the Riau Islands, Indonesia, with its capital being Bandar Sri Bentan. Meanwhile, Karimun has its capital, Tanjung Balai Karimun, and has been known for several centuries throughout the archipelago and abroad. Based on this position, Bintan and Karimun are border tourist areas for tourists from Singapore, Malaysia and other foreign countries. Therefore, Bintan and Karimun need to continue to improve to become border tourist areas apart from other cities in the Riau Islands province. This research aims to examine the behavior of border tourists, whether distance, tourist attractions and culture motivate them to visit the area. The research was carried out with the unit of analysis, namely in the border tourist area originating from Singapore and Malaysia who visited Bintan and Karimun in the main entrance area (entry point) to be studied and then draw conclusions. The research method used in this research is a quantitative method, with data collection techniques carried out using questionnaires. The sample was determined using the Slovin formula and obtained 250 respondents. The data obtained was then analyzed descriptively using SEM[1]AMOS to strengthen the research results using continium lines